Strategi Komunikasi Interpersonal Guru Bimbingan dan Konseling dalam Penanganan Permasalahan Siswa di Madrasah Aliyah - Azmi Azmi; Alfian Tanjung; Fenny Mustika Piliang (MAN 4 Kota Pekanbaru, 2026)
This study examines the interpersonal communication strategies employed by guidance and counseling teachers in handling students’ problems at MAS Miftahul Falah Diski. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving guidance and counseling teachers, school administrators, and students. The findings reveal that student problems range from moderate issues, such as truancy, classroom misconduct, and peer conflicts, to more serious cases, including pregnancy outside marriage. To address these problems, guidance and counseling teachers implement interpersonal communication through face-to-face interactions, empathetic listening, counseling sessions, and mediation between students and parents. These strategies help students express their concerns openly and facilitate problem resolution. However, several obstacles were identified, including students’ reluctance to disclose personal issues, emotional conditions during counseling sessions, and differences in perspectives between teachers and parents. The study highlights the importance of interpersonal communication as an effective approach in guidance and counseling services to support students’ personal and social development.